Exploring the Critical in Critical Approaches to Language Education - Mitsikopoulou, Bessie (The Greek Review of Social Research, 2025)
The article explores how the term critical is interpreted across four key approaches to language education: critical thinking, critical pedagogy, critical literacy, and critical language awareness. It examines the theoretical principles, epistemological assumptions, and pedagogical goals of each, highlighting both convergences and differences. Particular attention is given to the kinds of learners and citizens each approach seeks to cultivate. The analysis encourages reflection on how criticality is understood and enacted in diverse educational contexts, offering insights for more coherent and transformative language teaching practices.